2008
DOI: 10.5089/9781451870633.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Macroeconomic, Political, and Institutional Factorson the Structure of Government Debt in Emerging Market Countries

Abstract: This Working Paper should not be reported as representing the views of the IMF.The views expressed in this Working Paper are those of the author(s) and do not necessarily represent those of the IMF or IMF policy. Working Papers describe research in progress by the author(s) and are published to elicit comments and to further debate.Debt crises that have shaken Latin America, Asia, and Russia have brought an increasing attention to the structure of debt in emerging market countries. Using the newly released Jea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 13 publications
0
18
1
Order By: Relevance
“…Countries with high and very high levels of inflation are less able to borrow on easy terms. Guscina (2008) shows that low and stable inflation is associated with higher domestic debt share in total central government debt. On the other hand, Forslund et al, (2011) find that inflationary history has no statistically significant effect on the composition of government debt.…”
Section: Macroeconomic Determinants Of Government Debtmentioning
confidence: 99%
“…Countries with high and very high levels of inflation are less able to borrow on easy terms. Guscina (2008) shows that low and stable inflation is associated with higher domestic debt share in total central government debt. On the other hand, Forslund et al, (2011) find that inflationary history has no statistically significant effect on the composition of government debt.…”
Section: Macroeconomic Determinants Of Government Debtmentioning
confidence: 99%
“…For example, an empirical study by Mehl and Reynaud (2008) found the domestic "original sin" to be closely related to high inflation, high debt service-to-GDP ratio and narrow investor base. Using the same dataset as the one used in this paper, Guscina (2008) showed that domestic "original sin" decreases with the level of financial development, improvement in the quality of institutions, and achievement of macroeconomic stability. …”
Section: A Stylized Factsmentioning
confidence: 99%
“…As noted in Guscina (2008), there seems to be a certain threshold level of inflation that induces government to issue CPI-indexed debt.…”
mentioning
confidence: 99%
“… See Anaya and Pienkowski (2015) for an analysis of debt dynamics concerning public debt.11See Adler, Magud, and Werner (2017) for an empirical analysis on terms of trade cycles and the external adjustment.12 SeeGuscina (2008) for an analysis on the impact of political and institutional factors on the structure of government debt in emerging markets.©International Monetary Fund. Not for Redistribution…”
mentioning
confidence: 99%